Implementation of Civil Servant Competency Development in Improving Public Services in Bogor City Based on Perwal No. 78/2012 - Revaldi Wahyu Aji Nugraha; Andi Muhammad Asrun; Astim Riyanto (Publikasi Indonesia, 2024)
The Bogor City Regional Government intends to provide legal certainty in the relationship between the community and organizers of public services through Bogor City Regulation No. 78 of 2012 concerning the Implementation of Public Services within the Bogor City Government. The methods used in this study are a normative juridical approach that emphasizes literature research, namely examining legal materials obtained from literature research only, and do not require the preparation or formulation of hypotheses. Results Optimal public services can be created if the implementing apparatus receives sufficient competency development as mandated by Article 203 Paragraphs (3) and (4) Government Regulation No. 17 of 2020 concerning Amendments to Government Regulation No. 11 of 2017 concerning Management of Civil Servants. Based on the rights of civil servants as explained above and the results of previous research, there are contradictions in the implementation of civil servant competency development which make it not optimal, which should be suspected. Conclusion of human resource development that pays attention to the competency aspect produces elements of a quality, consistent, effective working relationship, the achievement of organizational goals, and the organization continues to exist in a competitive business environment and is also associated with the theory of public service which is a series of activities in order to meet service needs by laws and regulations for every citizen and resident of goods, services, and/or administrative services provided by public service providers.